Nutritional Composition, Sensory Quality and Consumer Acceptability of Beef Sausage Fortified With Edible Meat Waste - Babatunde Oluwasegun Alao; Andrew Bamidele Falowo (Turkish Journal of Agriculture: Food Science and Technology)
This study assessed the proximate composition, sensory quality and consumer acceptability of beef sausage fortified with edible meat waste. Lean beef and edible meat waste (EMW) samples were obtained from commercial abattoir and combined in ratio 50:50 and 70:30 and designated as T1 and T2 respectively, while CT contained 90% lean meat and 10% fat. The fresh T1, T2 and CT sausages were thermal processed using microwave and oven-grilling cooking methods. The results showed significant difference in moisture, protein, lipid and ash content of raw and cooked sausages across treatments. Raw sausage fortified with EMW had higher protein and lower lipid contents compared to control treatment (90/10, CT). Cooking of the sausage significantly decreased moisture and increase lipid, protein and lipid content, with microwaved sausage having higher values. The results of sensory quality showed that beef sausage fortified with EMW were all acceptable to consumers, irrespective of the cooking methods used. The distribution of consumers who liked the appearance, colour, texture and flavour of the sausage meat containing EMW were higher than those who dislike the products. Therefore, this study shows that EMW could be successfully used in meat industry to improve quality of sausage during production.